2015
DOI: 10.1152/ajplung.00252.2014
|View full text |Cite
|
Sign up to set email alerts
|

Vasculopathy and pulmonary hypertension in sickle cell disease

Abstract: Sickle cell disease (SCD) is an autosomal recessive disorder in the gene encoding the β-chain of hemoglobin. Deoxygenation causes the mutant hemoglobin S to polymerize, resulting in rigid, adherent red blood cells that are entrapped in the microcirculation and hemolyze. Cardinal features include severe painful crises and episodic acute lung injury, called acute chest syndrome. This population, with age, develops chronic organ injury, such as chronic kidney disease and pulmonary hypertension. A major risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 97 publications
2
104
0
3
Order By: Relevance
“…Chronic inflammation, intravascular haemolysis, imbalanced vascular nitric oxide (NO), oxidative stress are known factors that underlie vasculapathy-related complications in SCD [61,62]. Among these complications, pulmonary hypertension (PHT) and stroke stand out as the most prevalent and devastating.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation, intravascular haemolysis, imbalanced vascular nitric oxide (NO), oxidative stress are known factors that underlie vasculapathy-related complications in SCD [61,62]. Among these complications, pulmonary hypertension (PHT) and stroke stand out as the most prevalent and devastating.…”
Section: Discussionmentioning
confidence: 99%
“…The many clinical manifestations in SCD patients include recurrent vaso-occlusive episodes mediated by heterotypic cell-cell adhesion/aggregation, which cause pain crises and increase mortality due to organ damage and acute chest syndrome. 3,4 Hydroxyurea, an important therapy for SCD, induces production of fetal hemoglobin and also has other beneficial effects, including increasing nitric oxide (NO) species and decreasing the level of soluble vascular P revious studies identified the Ser/Thr protein kinase, AKT, as a therapeutic target in thrombo-inflammatory diseases. Here we report that specific inhibition of AKT with ARQ 092, an orally-available AKT inhibitor currently in phase Ib clinical trials as an anti-cancer drug, attenuates the adhesive function of neutrophils and platelets from sickle cell disease patients in vitro and cell-cell interactions in a mouse model of sickle cell disease.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, adults with SCD develop progressive vasculopathy, characterized by pulmonary artery endothelial dysfunction, intimal and smooth muscle and adventitia proliferation leading to PH. 9,10 Prevalence and HemodynamIc cHaracterIstIcs of Pulmonary HyPertensIon In sIckle cell dIsease…”
Section: Introductionmentioning
confidence: 99%